Development of Android-Based Learning Media in Mathematics and Natural Sciences Philosophy Courses for Physics Education Students - Purwanti, Popi; Mayanty, Sri; Dewati, Maria; Andayanti, Westri (Navigation Physics : Journal of Physics Education, 2025)
MIPA Philosophy is a course that discusses the basics of the philosophy of science, especially in the context of Mathematics and Natural Sciences (MIPA). The learning media used in Mathematics and Natural Sciences philosophy courses for physics education students generally only use Power Point (PPT), papers and presentations. Conventional learning methods may be less effective in generating interest and increasing student understanding. Therefore, more interactive and interesting learning media are needed to help students understand the material better. This research aims to develop Android-based learning media for the Mathematics and Natural Sciences Philosophy course in the UNINDRA Physics Education Study Program. The development model in this research uses ADDIE, which includes Analysis, Design, Development, Implementation and Evaluation. The results of trials carried out on students obtained an average score of 89.95% with the interpretation "very feasible". These results can be concluded that Android-based learning media in Mathematics and Natural Sciences philosophy courses is very suitable to be used as a medium in the learning process.